Ecosystem‐based environmental flow assessment in a Greek regulated river with the use of 2D hydrodynamic habitat modelling. (2nd May 2018) - Theodoropoulos, C.; Skoulikidis, N.; Rutschmann, P.; Stamou, A.
Abstract: Despite the long‐term research on the use of hydraulic‐hydrodynamic habitat models (HHMs) for predicting the response of aquatic biota to habitat alteration, their practical application in model‐based environmental flow assessments (EFAs) has been limited due to reasons mainly associated with cost‐effectiveness, time‐efficiency, required expertise, and availability of hydroecological information. In this study, we demonstrate a cost‐effective and time‐efficient application of a benthic‐invertebrate, two‐dimensional, fuzzy rule‐based EFA in a 277‐m long reach in the downstream route of a regulated river in western Greece. Apart from developing ecosystem‐based environmental flow (eflow) scenarios, we highlight the valuable features of HHMs, comment on their disadvantages, and propose working solutions to overcome them. The results of the study show that the hydrology‐based eflow of 0.2 m 3 /s, initially proposed by the managing authorities, is not sufficient to ensure the long‐term functionality of the downstream benthic communities, as the ecosystem‐based eflow ranged between 0.6 and 2 m 3 /s. As social resilience relies heavily on ecological resilience, ecosystem‐based approaches can ensure the sustainability of aquatic ecosystems. This study demonstrates, inter alia, that HHMs‐based EFAs can be implemented cost‐effectively and time‐efficiently to serve as an accurate scientific basis for water managers and stakeholders, in search of the fine balance between anthropogenic water demand and long‐term ecosystem integrity and functionality.